Fresno Merced Counties Legal Services Office Holiday Party - Watkins, Howard::::::::: (1982)
Office Christmas tree, Howard Watkins dressed as Santa Claus with several young children, Marilyn Williams on floor; in background: guest and Janie Munoz seated